2006
DOI: 10.1111/j.1468-2419.2006.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of learning from management development programmes: testing the Holton model

Abstract: gies to deal with them. It can also be used as a framework for the evaluation of training and development interventions, examining factors outside the traditional range of most training evaluation efforts and providing a more complete picture of the success or otherwise of that intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(192 citation statements)
references
References 41 publications
13
176
1
2
Order By: Relevance
“…In consequence, three hypotheses were formulated: Working Alliance Determinants Related to the Coachee. In both psychotherapy and management training, the results of numerous studies indicate that the participant' s motivation in any developmental process is related to its outcome (Axtell, Maitlis, & Yearta, 1997;Kirwan & Birchall, 2006;Schneider & Klauer, 2001). However, to our knowledge no research has made an indepth analysis of the relationship between the coachee' s motivation and the working alliance.…”
Section: The Coach-coachee Relationship In Executive Coachingmentioning
confidence: 99%
“…In consequence, three hypotheses were formulated: Working Alliance Determinants Related to the Coachee. In both psychotherapy and management training, the results of numerous studies indicate that the participant' s motivation in any developmental process is related to its outcome (Axtell, Maitlis, & Yearta, 1997;Kirwan & Birchall, 2006;Schneider & Klauer, 2001). However, to our knowledge no research has made an indepth analysis of the relationship between the coachee' s motivation and the working alliance.…”
Section: The Coach-coachee Relationship In Executive Coachingmentioning
confidence: 99%
“…The LTSI is a validated transfer system inventory including 16 factors composed of 68 items measuring individual, intervention, and work environment factors (with an additional 21 items under review to increase reliability). Although the LTSI provides an initial assessment of trainee perceived factors impacting transfer and is effective for planning purposes in the posttraining context, it does not measure transfer directly thus limiting inferences concerning relationships with transfer outcomes (Kirwan & Birchall, 2006).…”
Section: Guiding Future Transfer Researchmentioning
confidence: 99%
“…However, 3 transfer of learning does not always occur. Many organisations have found that about 10% to 20% of training is ever applied in the real world (Ford, 2009;Kirwan & Birchall, 2006). Failure to transfer learning occurs for several reasons and these may be grouped as factors within the student, design of the learning sessions, and organisational climate or workplace environment.…”
Section: Introductionmentioning
confidence: 99%